Penerapan Metode Multifactor Evaluation Process (MFED) Dengan Pembobotan Metode Rangking Dalam Penyeleksian Murid Masuk Kelas Tahfizd SMP Swasta Muhammadiyah-24 Aek Kanopan - Dicky Marsella; Eferoni Ndruru; Fadlina Fadlina (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Aek Kanopan Muhammadiyah-24 Private Junior High School is known as MUHADAPAT with the Motto "Islamic, Intelligent, Superior, Achievement". This Tahfizd class is one of the classes with the highest number of registrants increasing every year, seen from previous years. In this case the selection of students entering the tahfizd class of Private Junior High School Muhammadiyah-24 Aek Kanopan However, there are obstacles in selecting students to enter the tahfizd class, because determining the selection results is still manually. So it is necessary to develop a system that can provide recommendations based on the ranking of student selection by applying the MFEP method. The method used in this study is the Multifactor Evaluation Process (MFEP). This method can guarantee to make it easier to determine the selection of students to enter the tahfizd class.